Strategi Efektif Orang Tua Dalam Merangsang Perkembangan Bahasa Arab Anak - Bayzura, Septika; Setiyawan, Agung (STIQ Amuntai, 2024)
This study aims to describe and explain about children's language development and its stages. Factors of children's language development, as well as effective strategies for parents in helping children's language development. The research method used is descriptive qualitative research using a literature approach in an effort to describe, record and analyze and interpret the current conditions. The data sources in this study are literature such as books, journals, articles, or documents that discuss effective strategies or the role of parents in stimulating children's language development. Data analysis is done by data reduction, data presentation, and conclusion drawing. The results of this study show that there are two factors that influence children's language development, namely internal and external. And explained that there are several effective strategies that can be used by parents in helping stimulate children's language development such as talking and interacting actively, reading books together, singing, creating a language-rich environment, using educational media, using rich and varied language, and consistency in learning and language development